Peer Counselor Training for High School Students in West Jakarta - Risnawaty, Widya; Kartasasmita, Sandi; Suryadi, Denrich (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
The present community service activities were held to provide peer counselor training for high school Students in West Jakarta. Results from our survey showed several problems such as high achievement demand from parents, disparity between peer groups, and verbal abuse from parents. Despite these problems, students prefer to share their problems with their peers to consulting their problems with the Guidance and Counseling (GC) teacher, subject teacher, or homeroom teacher. To address this problem, the solution offered was to prepare assistance for GC teachers by giving training to selected students so that they are able to help other students, that is as peer counselors. Students who were trained must pass a selection process to meet standard qualifications as peer counselors. The peer counselor training aimed to provide competency-based knowledge and skills as a counselor. The task of these peer counselors was to act as peer assistants who can accommodate stories and complaints from peers based on basic counselling skills. Peer counselors are expected to help reduce psychological tension experienced by peers in need. The implementation stages included the following: socializing the program, implementation of training with 14 sessions, practices and supervisions, and evaluation program. Through the training, the students were successfully introduced to simple theories and counseling skills to trainees. After 6 simulated exercises, each participant experienced better counseling skills. However, to keep improving their skills, it is necessary that the trainees be given a periodic training and a strong support from the school, especially from GC teachers.